Birokrasi Pemicu Tindakan Kekerasan Petugas di Pelabuhan Indonesia - Elfrida Gultom (Universitas Islam Indonesia, 2006)
The duty of harbor is very lmportant and it serves services to ships that act activities for instance, goods, passengers, etc. The services in Indonesian harbors tend to be unqualified, high cost economy. Based on the result of the research revealed that the fundamental problerhs In this context is behavior of involved person in applying the function in harbor, namely corruption, and it implies to reduce state Income. The sup porting of this phenomenon is birocracy in unqualified services. This condition causes the activities of harbour uncoducively and can not reach the aim to increase national growth economy and prosperous Indonesian people.